Food Chains and Food Webs in Aquatic Ecosystems - Park, Young-Seuk; Kwak, Ihn-Sil (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Food webs describe the structure of communities and their energy flows, and they represent interactions between species in ecosystems. Recently, we have witnessed rapid development of techniques for both experimental studies and theoretical/computational studies on food webs as well as species interactions. This reprint book is focused on food chains and food webs in aquatic ecosystems, with seven papers published in the corresponding Special Issue of Applied Sciences. The topics include empirical studies on food chains and food webs as well as effects of environmental factors on organisms in aquatic ecosystems.